Empathy Is a Protective Factor of Burnout in Physicians: New Neuro-Phenomenological Hypotheses Regarding Empathy and Sympathy in Care Relationship - Thirioux, Bérangère; Birault, François; Jaafari, Nematollah (Frontiers in Psychology, 2016)
Burnout is a multidimensional work-related syndrome that is characterized by emotional exhaustion, depersonalization – or cynicism – and diminution of personal accomplishment. Burnout particularly affects physicians. In medicine as well as other professions, burnout occurrence depends on personal, developmental-psychodynamic, professional and environmental factors. Recently, it has been proposed to specifically define burnout in physicians as “pathology of care relationship”. That is, burnout would arise, among the above-mentioned factors, from the specificity of the care relationship as it develops between the physician and the patient. Accordingly, experimental studies and theoretical approaches have suggested that burnout and empathy, which is one of the most important skills in physicians, are closely linked. However, the nature of the relation between burnout and empathy remains not yet understood, as reflected in the variety of theoretical and contradictory hypotheses attempting to causally relate these two phenomena. Firstly, we here question the epistemological problem concerning the modality of the burnout-empathy link. Secondly, we hypothesize that considering the multidimensional features of both burnout and empathy, on one hand, and on the other hand, the distinction between empathy and sympathy enables to overcome these contradictions and, consequently, gives a better understanding of the relationship between burnout and empathy in physicians. Thirdly, we propose that clarifying the link between burnout, empathy and sympathy would enable developing specific training in medical students and continuous professional formation in senior physicians and would potentially contribute to the prevention of burnout in medical care.